Unity and Harmony? Tensions and approaches between fascists and antifascists in Bahía Blanca’s Italian mutualism (Argentina, 1929-1932) (Quinto Sol, 2023)
This article analyzes the attempts made from 1929 -in the midst of an increasing economic and institutional crisis of Italian mutualism in Bahía Blanca (Argentina)- by the antifascist leadership of the Sociedad de Socorros Mutuos e Instrucción Italia Unita and the Italian Vice Consulate to settle the differences that had been keeping them apart since 1927. Likewise, the article studies the final consequences of those attempts that, by 1932, led to the impossibility of reestablishing relations, as a result of the political course within the only Italian mutual institution in the city. The source corpus, formed by Italian and Argentine documents, and made up from press, institutional documentation and Italian state’s inner reports, allows for a juxtaposition of information that permits to create a perspective in local scale, which focuses on the complexity everyday politics in the Italian community.The approach to episodes of cooperation between fascists and antifascists within a mutual institution, as well as the elements that made it impossible to thrive, allows to contribute to the studies of political reality in the Italian community during the fascist ventennio, by tinging views that tend to see both ideological groups as irreconcilable antagonists.
Keywords: Fascism; Antifascism; Mutualism; Italian community